2015
DOI: 10.1007/s00296-015-3381-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on clinical and radiographic variables, and acute phase reactants in patients with ankylosing spondylitis

Abstract: To investigate the association between smoking and clinical, inflammatory and radiographic parameters in patients with ankylosing spondylitis (AS). One hundred and six tumour necrosis factor inhibitor naïve patients with AS were included in the study. The erythrocyte sedimentation rate, C-reactive protein, Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI) and modified Stroke AS Spine Score (mSASSS) were assessed cross-sectionally for each patient. Smoking history was obtained, and smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…This could not be explained by age or gender (factors associated with radiographic progression); current smokers were younger with shorter disease and symptom duration and did not have more males than other groups. Other studies have reported greater radiographic progression in AS smokers [9, 10, 12]. …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This could not be explained by age or gender (factors associated with radiographic progression); current smokers were younger with shorter disease and symptom duration and did not have more males than other groups. Other studies have reported greater radiographic progression in AS smokers [9, 10, 12]. …”
Section: Discussionmentioning
confidence: 92%
“…The three remaining studies reported no associations between markers of disease severity and pack-years [11, 12, 16]. There are several possible explanations for the inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more the patients smoke the more they kept the disease active because the tobacco acts by causing the inflammation from where staying smoker keeps the inflammation but it was not possible to say whether it depended on the intensity of the smoking It was not possible to collect data on the basis of number of packets per day or per week to have the number of packets accumulate over the year.This seems to be the object of several studies in the literature that have become more Based on the influence of smoking on the activity of spondyloarthritis, in particular the effect of smoking on the activity of spondyloarthritis [17, 18, 23-27]. They demonstrated that smoking AS patients had significantly higher activity by the BASDAI scores [3, 14-24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smoking appears among the factors associated with an increased risk of advanced disease, higher activity and early onset of inflammatory back pain in young patients [17, 18]. …”
Section: Introductionmentioning
confidence: 99%